2019
DOI: 10.3390/app9020296
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Massive Deployment Solution Based on the Peer-to-Peer Protocol

Abstract: : The BitTorrent (BT) is a peer-to-peer (P2P) file sharing protocol that was developed approximately 20 years ago, is becoming increasingly popular, and has been widely accepted. The BT-based mass deployment system can be used to improve performance and scalability that cannot be achieved by the unicasting, broadcasting, and multicasting protocols. However, when the BT-based system is applied in massive deployments, a major issue related to insufficient temporary storage space to store the whole system image b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 45 publications
0
21
1
Order By: Relevance
“…P2P is actually not a brand-new kind of modern technology. In reality, it is has actually been around considering that the advancement of the Internet where it originated with the e-mail process [10]. A P2P is a network of computers that each share an equal volume of responsibility in relation to process a data as shown in Figure 1.…”
Section: Peer To Peer (P2p)mentioning
confidence: 99%
“…P2P is actually not a brand-new kind of modern technology. In reality, it is has actually been around considering that the advancement of the Internet where it originated with the e-mail process [10]. A P2P is a network of computers that each share an equal volume of responsibility in relation to process a data as shown in Figure 1.…”
Section: Peer To Peer (P2p)mentioning
confidence: 99%
“…Because of the limitation of the network protocol, the multicast solution is not scalable. Our previous studies [3], [10] have revealed that the network-based deployment system using unicast, broadcast, and multicast mechanisms have some drawbacks. Such systems cannot be enhanced to achieve good efficiency and scalability.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems cannot be enhanced to achieve good efficiency and scalability. The BT deployment mechanism from an image (BDMfaI) solution proposed in our previous study [10] was based on the BitTorrent (BT) protocol [11], a P2P [12] file-sharing technology developed approximately 20 years ago. The BDMfaI has provided a robust and scalable scheme for massive deployment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations